Estimating survival in patients with gastrointestinal cancers and brain metastases: An update of the graded prognostic assessment for gastrointestinal cancers (GI-GPA). (September 2019) - Sperduto, Paul W.; Fang, Penny; Li, Jing; Breen, William; Brown, Paul D.; Cagney, Daniel; Aizer, Ayal; Yu, James B.; Chiang, Veronica; Jain, Supriya; Gaspar, Laurie E.; Myrehaug, Sten; et al.
Highlights: Brain metastases in GI cancer patients are not uncommon. Survival varies widely within this cohort. New identified prognostic factors are incorporated in an updated prognostic index. This index, the GI-GPA, will better estimate survival. The GI-GPA is useful in treatment selection and stratification of clinical trials. Abstract: Background: Patients with gastrointestinal cancers and brain metastases (BM) represent a unique and heterogeneous population. Our group previously published the Diagnosis-Specific Graded Prognostic Assessment (DS-GPA) for patients with GI cancers (GI-GPA) (1985–2007, n = 209). The purpose of this study is to update the GI-GPA based on a larger contemporary database. Methods: An IRB-approved consortium database analysis was performed using a multi-institutional (18), multi-national (3) cohort of 792 patients with gastrointestinal (GI) cancers, with newly-diagnosed BM diagnosed between 1/1/2006 and 12/31/2017. Survival was measured from date of first treatment for BM. Multiple Cox regression was used to select and weight prognostic factors in proportion to their hazard ratios. These factors were incorporated into the updated GI-GPA. Results: Median survival (MS) varied widely by primary site and other prognostic factors. Four significant factors (KPS, age, extracranial metastases and number of BM) were used to formulate the updated GI-GPA. Overall MS for this cohort remains poor; 8 months. MS by GPA was 3, 7, 11 and 17 months for GPA 0–1, 1.5–2, 2.5–3.0 and 3.5–4.0, respectively. >30% present in the worst prognostic group (GI-GPA of ≤1.0). Conclusions: Brain metastases are not uncommon in GI cancer patients and MS varies widely among them. This updated GI-GPA index improves our ability to estimate survival for these patients and will be useful for therapy selection, end-of-life decision-making and stratification for future clinical trials. A user-friendly, free, on-line app to calculate the GPA score and estimate survival for an individual patient is available atbrainmetgpa.com .